Global Recovery and World Debt: An Address - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "Global Recovery and World Debt: An Address," written by Walter B. Wriston for the International Monetary Conference on 4 June 1984. The original speech is located in MS134.001.005.00021.